Investigating the histopathologic correlates of 18F-FDG PET heterogeneity in non-small-cell lung cancer. Issue 12 (December 2018) - Bashir, Usman; Foot, Oliver; Wise, Olga; Siddique, Muhammad M.; Mclean, Emma; Bille, Andrea; Goh, Vicky; Cook, Gary J.
Abstract : Purpose: Despite the growing use of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET texture analysis to measure intratumoural heterogeneity in cancer research, the biologic basis of 18 F-FDG PET-derived texture variables is poorly understood. We aimed to assess correlations between 18 F-FDG PET-derived texture variables and whole-slide image (WSI)-derived metrics of tumour cellularity and spatial heterogeneity. Patients and methods: Twenty-two patients with non-small-cell lung cancer prospectively underwent 18 F-FDG PET imaging before tumour resection. We tested nine 18 F-FDG PET parameters: metabolically active tumour volume, total lesion glycolysis, mean standardized uptake value (SUVmean ), first-order entropy, energy, skewness, kurtosis, grey-level co-occurrence matrix entropy and lacunarity (SUV-lacunarity). From the haematoxylin and eosin-stained WSIs, we derived mean tumour-cell density (MCD) and lacunarity (path-lacunarity). Spearman's correlation analysis and agglomerative hierarchical clustering were performed to assess variable associations. Results: Tumour volumes ranged from 2.2 to 74 cm 3 (median: 17.9 cm 3 ). MCD correlated positively with total lesion glycolysis ( r s : 0.46, P : 0.007) and SUVmean ( r s : 0.55; P : 0.008) and negatively with skewness and kurtosis ( r s : −0.47 for both; P : 0.028 and 0.026, respectively). SUV-lacunarity and path-lacunarity were positively correlated ( r s : 0.5; P : 0.018). On cluster analysis, larger tumours trended towards higher SUVmean and entropy with a predominance of tightly concentrated high SUV-voxels (negative skewness and low kurtosis on the histogram); on WSI analysis such larger tumours also displayed generally higher MCD and low SUV-lacunarity and path-lacunarity. Conclusion: Our data suggest that histopathological MCD and lacunarity are associated with several commonly used 18 F-FDG PET-derived indices including SUV-lacunarity, metabolically active tumour volume, SUVmean, entropy, skewness, and kurtosis, and thus may explain the biological basis of 18 F-FDG PET-uptake heterogeneity in non-small-cell lung cancer. Abstract : Supplemental Digital Content is available in the text.